Factors associated with post-delivery complications, according to the demographic and family health survey in Perú 2019-2020: Factores asociados a complicaciones post parto según la encuesta demográfica y de salud familiar en Perú 2019-2020 - Mauricio-Fernández, Kimberley Lissette (2023)
Introducción: Las complicaciones post parto son problemas de salud importante en el Perú, por lo tanto, es necesario determinar sus factores asociados. Objectives. To determine the factors associated with complications after childbirth in women aged 12 to 49 years in Peru, according to the demographic and family health survey, 2019-2020. Methods. Secondary source study based on the ENDES 2019-2020. The unit of analysis was all women aged 12 to 49 years residing in Peru in the years 2019-2020, who presented postpartum complications, and who answered the questions of the study variables. Results. It is evidenced that the age of 20 to 35 years has a prevalence ratio of 1.12 of ending in complications after delivery (RPa: 1,12, 95% CI: 1,07 to 1,18). Having complications during delivery has 2.75 times the prevalence of complications after delivery (RPa: 2,75, 95% CI: 2,64 to 2866). Having primary education (RPa: 0,90, 95% CI: 0,84 to 0,96), secondary (RPa: 0,94, 95% CI: 0,89 to 0,98) and single marital status (RPa 0,85, 95% CI: 0,76 to 0,94) decrease the probability of having complications after of childbirth. Conclusion. The prevalence of complications after delivery is 37,7%. Factors associated with complications after childbirth are: age, level of education, civil status and complications during delivery.